1971
DOI: 10.1084/jem.134.6.1570
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism in the Macrophage

Abstract: Macrophage membrane cholesterol is present in two subcellular cholesterol pools, a rapidly exchanging compartment comprising about two-thirds of the total cholesterol, and a slowly exchanging compartment comprising one-third of the total. The morphological identification of the kinetically distinguishable pools proceeded by alteration of each compartment. Trypsin treatment markedly decreased the rate of cholesterol exchange without removing cholesterol from the membrane. Recovery of normal exchange rates took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…This value is quite high as compared with other cells (21,46), remains constant during in vitro cultivation, and is independent of the cholesterol content of the extraceUular medium (18,51,52). The macrophage does not divide under these conditions but gradually increases in size, protein, enzyme content, and the amount of total free cholesterol.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This value is quite high as compared with other cells (21,46), remains constant during in vitro cultivation, and is independent of the cholesterol content of the extraceUular medium (18,51,52). The macrophage does not divide under these conditions but gradually increases in size, protein, enzyme content, and the amount of total free cholesterol.…”
Section: Discussionmentioning
confidence: 66%
“…Inhibitors of pinocytosis and protein synthesis had no effect on cholesterol incorporation during a 4 hr exposure in the presence of isotope. Puromycin and cycloheximide had significant effects after 5 hr of continuous exposure (46). Both subcellular compartments were labeled in the presence of the inhibitors.…”
Section: Effect Of Serum Concentration On the Kinetics Of Exchange--mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a number of storage diseases in which cholesterol accumulates in tissues, although the lesion is not known to involve cholesterol metabolism. We have demonstrated that net increases in both cholesterol and phospholipid can be considerable in cells containing storage granules, the contents of which are free of lipid (2). These increases are due to the membrane of the secondary lysosomes.…”
Section: Fate Of Free Cholesterol--the Results Indicate That Phagocymentioning
confidence: 92%
“…Since the value of the rate constant k32 describing the relative movement of cholesterol from the lysosomal membrane to the plasma membrane during exchange is similar in value to k~, the rate-limiting reaction probably occurs at the same step for both exchange and excretion. In the absence of membrane apposition or translocation, an intracellular soluble "carrier" may mediate the transfer of cholesterol between the lysosomal membrane and the plasma membrane (2). Cholesterol may therefore move from within the lysosome to the lysosomal membrane readily, whereas the transfer to the intracellular carrier, or its concentration may be rate limiting.…”
Section: Fate Of Free Cholesterol--the Results Indicate That Phagocymentioning
confidence: 99%